2017
DOI: 10.3906/vet-1604-14
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic electrode montage in goats: topographical, radiological, and physiological assessment

Abstract: The paucity of information on assortment of EEG leads in goats has hampered analysis of brain regional activity during different physiological, pathological, and ethological conditions in this species. Hence, the present study was designed to develop a montage with suitable combinations of EEG electrode arrays in goats. Ten specimens of freshly slaughtered goat heads (crossbreed of Jamunapari) were procured and preserved at -20 °C. Frozen samples were sliced sagittally and transversely to corroborate the link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Findings from domestic species were concluded to be in accordance with the general pattern [44]. Indeed, the general pattern found in ungulate livestock in the present review still seems to support the emotional valence hypothesis, at least with regard to fear, since vigilance or responses in novel and/ or fear inducing contexts were often found to be directed by the left eye/ ear or right nostril ( [59,67,68,86,96,98,107,114,117,140,144,149,150,166], but see [105,148] for contradictory findings). In contrast, right hemispheric dominance for aggression was only supported by findings in horses [67], while studies on agonistic behavior in cattle and pigs failed to find a bias at the population level [144,172].…”
Section: Emotional Processingsupporting
confidence: 81%
See 1 more Smart Citation
“…Findings from domestic species were concluded to be in accordance with the general pattern [44]. Indeed, the general pattern found in ungulate livestock in the present review still seems to support the emotional valence hypothesis, at least with regard to fear, since vigilance or responses in novel and/ or fear inducing contexts were often found to be directed by the left eye/ ear or right nostril ( [59,67,68,86,96,98,107,114,117,140,144,149,150,166], but see [105,148] for contradictory findings). In contrast, right hemispheric dominance for aggression was only supported by findings in horses [67], while studies on agonistic behavior in cattle and pigs failed to find a bias at the population level [144,172].…”
Section: Emotional Processingsupporting
confidence: 81%
“…In another study, goats were found to learn a maze task faster when they were trained to use the left alley to exit the maze, which suggests a left visual field (and therefore right hemisphere) advantage for learning [164]. Further evidence for an important role of the right hemisphere in learning comes from findings that the right hemisphere guides attention processes [124,166]. Also, foals that kept their mother in their left visual field had fewer spatial separations from their mother, which suggested that they maintained spatial proximity better due to a right hemisphere advantage in visuospatial processing [122].…”
Section: Cognitive Performance and Strategiesmentioning
confidence: 98%
“…The oscillation of the alpha and theta activities were related to the neuronal activities linking to the sensory and emotional processing. Animals in the relaxed states showed lower Ptot activities, higher theta activities, and decreased alpha waves ( Bergamasco et al, 2005 , Choi et al, 2015 , Madan et al, 2017 ). All goats except for those in the TS6L6 and TS6L12 showed a decrease in alpha activities.…”
Section: Discussionmentioning
confidence: 97%
“…Twelve healthy (Local X Barbari) female goats weighing 23.66 ± 2.22 kg, aged 2 to 4 years were kept under optimum managemental and environmental conditions throughout the experimental period, under the provisions of ethical treatment of experimental animals. Prior to the start of the experiment, all the goats were acclimatized to the experimental conditions as described (HUOZHA et al, 2009, MADAN et al 2017) until a uniform resting EEG was obtained. The relevant areas of electrode placement on the scalp were shaved aseptically one day before the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Electroencephalographic recordings. A sevenchannel monopolar montage: F3-Ref., (even number: right hemisphere, odd number: left hemisphere; F: Frontal; Cz: Vertex; P: Parietal; O: Occipital; R: Reference electrode) was used in the goats in sternal recumbency as described (MADAN et al, 2017) to record brain bioelectric activity. The leads were connected to the head box of the EEG recording instrument -RMS Brain View Plus (Recorder & Medicare Systems, Ambala method where the recorded waveforms reflect the cortical electrical activity generated by the brain cells in the time course of extracellular field potentials in a synchronous action.…”
Section: Methodsmentioning
confidence: 99%